The Preliminary Study on The Effect of Coarse Particles Content on OMC and Maximum Dry Unit Weight: A Case of Aceh’s Fill Materials - Bambang Setiawan (Aceh International Journal of Science and Technology, 2016)
Empirical evidence suggests that the percentage of coarse fraction content on soil has an influence on the soil optimum moisture content (OMC) and soil maximum dry density (MDD). This phenomenon is used as a basis to examine the characteristics of Aceh’s fill materials. The major objective of the present study is to determine the relationship between coarse-grained content and OMC and MDD of the Aceh’s fill materials. This relationship is important in the justification of soil suitability as materials for engineering construction. Thirty (30) soil samples from various locations in the Province of Aceh have been collected and tested. The tests carried out include soil physical properties tests and standard compaction test. In the case of a relationship between soil coarse fraction content and soil OMC or MDD, two general findings have been deduced. The first finding of the present study shows that the soil OMC decreases when the content of coarse-grained particles in the soil increases. The later finding shows a positive correlation between coarse particles content and the soil MDD which the increase of the content of coarse-grained particles in the soil will increase the value of the soil’s MDD. In conclusion, the coarse particles content affects the OMC and MDD of Aceh’s fill materials